Fraud Pentagon Theory dan Deteksi Kecurangan Laporan Keuangan: Pendekatan Beneish M-Score pada Sektor Perdagangan - Fatimah Azzahra F. Tamaela; Irfan Zamzam; Asrudin Hormati; Zainuddin Zainuddin (Owner : Riset dan Jurnal Akuntansi, 2025)
Financial statement fraud remains a serious concern that threatens the reliability of financial reporting and investor confidence. The Fraud Pentagon Theory identifies five elements that drive fraudulent behavior—pressure, opportunity, rationalization, competence, and arrogance—yet their empirical relevance may differ across industries. This study aims to examine the influence of these five elements, proxied by financial target, financial stability, nature of industry, auditor change, director change, and CEO duality, on financial statement fraud in trading sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Using purposive sampling, a total of 168 firm-year observations from 56 companies were analyzed, with financial statement fraud measured by the Beneish M-Score and logistic regression performed via SPSS 26. The results reveal that financial stability and the nature of industry significantly increase the likelihood of fraudulent financial reporting, while financial target, auditor change, director change, and CEO duality do not have a significant impact. These findings suggest that not all elements of the Fraud Pentagon are equally relevant in detecting financial statement fraud, highlighting the importance of contextual and industry-specific approaches in refining fraud risk assessment and contributing to the development of a more nuanced application of the Fraud Pentagon Theory in empirical research.